The effect of civil war violence on aid allocations in Uganda - Stijn van Weezel (University College Dublin, UCD School of Economics, 2017)
In recent years there has been an increase in the number of studies using microlevel data to analyse the aid-conflict nexus at local level, however most of these studies focus on how conflict dynamics are influenced by aid allocations whereas there is relatively little analysis on how conflict affects subnational aid allocations. Estimating the effect of conflict on aid can be difficult given possible reverse causality, therefore this study exploits an exogenous driven shock in conflict intensity in Uganda to estimate the effect of aid allocations at subnational level. Using district level data for Uganda between 2002-2010, and information on both foreign aid commitments and disbursements, the results show that conflict is negatively related to aid allocations: Conflict-struck regions see both lower commitment and disbursement levels in the wake of conflict. Although the sudden outburst of violence in Uganda can help identifying the effect of conflict on aid allocations, one caveat of this approach is that it is hard to know to what extent the results generalise.
Keywords: D74; F35; H72; N47; 330; civil conflict; foreign aid; Uganda; differences-in-differences